Pathway-Based Reduction of Repeat Head Computed Tomography for Patients With Complicated Mild Traumatic Brain Injury: Implementation and Outcomes. (18th November 2021) - Stippler, Martina; Keith, Stacey; Nelton, Emmalin B; Parsons, Charles S; Singleton, Jennifer; Bilello, Leslie A; Tibbles, Carrie D; Davis, Roger B; Edlow, Jonathan A; Rosen, Carlo L
Graphical Abstract: